Microwave and Radio-Frequency Technologies in Agriculture an Introduction for Agriculturalists and Engineers. - Brodie, Graham (Online access: De Gruyter De Gruyter Open Books., 2016)
Humanity faces the looming challenge of feeding more people, with less labour and resources. Early adoption of biological and physical technologies has allowed agriculturalists to stay a step ahead of this challenge. This book provides a glimpse of what is possible and encourages engineers and agriculturalists to explore how radio-frequency and microwave systems might further enhance the agricultural industry.